Biaya dan Kualitas Penyehatan Lingkungan Rumah Sakit Umum Di Daerah Istimewa Yogyakarta (Sanitasi: Jurnal Kesehatan Lingkungan, 2009)
A hospital is a public facility which has highly possibilities to get nosocomial in-fection and pollution of the surrounding environmental from its daily activities. In order to avoid and to decrease those kinds of risks, a hospital is necessary to carry out environmental health programs and those activities were based on the Ministry of Health’s decision Number 1204/ Menkes/SK/X/2004. This study has used analytic descriptive research using cross sectional design. The vari-ables which were studied compare between total cost of investment cost, operational cost, maintenance cost, and administration cost. In addition, the output quantity of activities was the amount of water which was produced (m3), the amount of waste water which was treated (m3), the amount of which was annihilated (kg), and the volume of room which was sterilized (m3), while the output quality consisted of quality of laboratorial diagnostic result based on the request from every sanitation installation which is inline with the parameter request. Furthermore, unit cost was the total cost that is divided by output qu-antity.To accomplish the quality of bacteriology in water supply is not as good as the quality of its chemistry and physics and also the quality of microbiology at waste water treatment. Otherwise, to handle the quality of microbiology is easier in technology and cheaper in cost side if comparing to handle the quality of chemistry and physics. The cost of fuel in destroying the solid medical waste becomes the highest cost so it is needed an efficient fuel of burner. To ac-complish the quality of sterilization result so standart operating procedure accomplishment becomes important. The average of actual unit cost for pro-cessing healthy water is Rp 854/m3, while for recycling waste water, proces-sing of solid medical wasted, and sterilization are Rp 9.341/m3, Rp 6.957/kg, and Rp 1.650/m3 respectively. The higher the unit cost for water supply the better the quality of microbiology and physics. In waste water treatment, the higher unit cost the better the quality of bacteriology and chemistry. Otherwise for sterilization, the less sterilized room volume the higher the unit cost.